Electric vehicle battery thermal management system with thermoelectric cooling - Y. Lyu; A. R. M. Siddique; S. H. Majid; M. Biglarbegian; S. A. Gadsden; S. Mahmud (Energy Reports, 2019)
An experimental investigation is performed on an advanced battery thermal management system for emerging electric vehicles. The developed battery thermal management system is a combination of thermoelectric cooling, forced air cooling, and liquid cooling. The liquid coolant has indirect contact with the battery and acts as the medium to remove the heat generated from the battery during operation. Forced air assisted heat removal is performed from the condenser side of the thermoelectric liquid casing. Detailed experiments are carried out on a simulated electric vehicle battery system. Experimental results reveal a promising cooling effect with a reasonable amount of power dissipation. Moreover, the experimental test shows that the battery surface temperature drops around 43 C (from 55 C to 12 C) using TEC-based water cooling system for a single cell with copper holder when 40 V is supplied to the heater and 12 V to the TEC module.
Keywords: 330; Battery thermal management; Electric vehicle; Heater; Li-ion battery; Thermoelectric cooling